ANALYSIS AND APPLICATION OF SYMMETRICAL TOGGLE-LEVEL PARALLEL MECHANISM - LU Lin (Jixie qiangdu)
A new parallel symmetric mechanism that can get greater output force was introduced in this article,which was composite of the lever force increasing mechanisms bearing a length effect and the toggle force increasing mechanism based on an angle effect. The working principle of the mechanism was explained in detail,meanwhile,the mechanical analyses were carried out and the characteristic curves were drawn. Finally,the application of this mechanism was given. The mechanism was simple and high-efficiency because it was parallel in construction and function in series.